Objectivization study of acupuncture Deqi and brain modulation mechanisms: a review - Zhong, Zhen; Yao, Lin; Liu, Yan-Ze; Wang, Yu; He, Min; Sun, Meng-Meng; Huang, Hai-Peng; Ma, Shi-Qi; Zheng, Hai-Zhu; Li, Meng-Yuan; Zhang, Xin-Yu; Cong, De-Yu; et al. (Frontiers in Neuroscience, 2024)
Deqi is an important prerequisite for acupuncture to achieve optimal efficacy. Chinese medicine has long been concerned with the relationship between Deqi and the clinical efficacy of acupuncture. However, the underlying mechanisms of Deqi are complex and there is a lack of systematic summaries of objective quantitative studies of Deqi. Acupuncture Deqi can achieve the purpose of treating diseases by regulating the interaction of local and neighboring acupoints, brain centers, and target organs. At local and neighboring acupoints, Deqi can change their tissue structure, temperature, blood perfusion, energy metabolism, and electrophysiological indicators. At the central brain level, Deqi can activate the brain regions of the thalamus, parahippocampal gyrus, postcentral gyrus, insular, middle temporal gyrus, cingulate gyrus, etc. It also has extensive effects on the limbic-paralimbic-neocortical-network and default mode network. The brain mechanisms of Deqi vary depending on the acupuncture techniques and points chosen. In addition, Deqi 's mechanism of action involves correcting abnormalities in target organs. The mechanisms of acupuncture Deqi are multi-targeted and multi-layered. The biological mechanisms of Deqi are closely related to brain centers. This study will help to explore the mechanism of Deqi from a local-central-target-organ perspective and provide information for future clinical decision-making.